The Effect of Gamma Radiation (60Co) on the Germination of Chili Pepper (Capsicum frutescens L.) - Bariyyah, Khoirul; Istianingrum, Putri; Rosyidi, Muhammad Abdul (Journal of Agriculture, 2025)
This study aimed to investigate the effect of various doses of gamma radiation (60Co) on the germination of Prentul chili pepper.  This research was conducted at the experimental field or greenhouse of the University of 17 August 1945, Banyuwangi, from August to September 2025. This study employed an RCBD with a single factor, namely the dose of ??Co gamma radiation. The treatment consisted of 11 radiation dose levels: 0 Gy (control), 50, 100, 150, 200, 250, 300, 350, 400, 450, and 500 Gy. The data obtained were analyzed using analysis of variance (ANOVA) to determine the effect of radiation dose on each parameter. If significant differences were found, further analysis was conducted using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. Co-60 gamma radiation significantly affected the viability, mortality, germination rate (MGT), and early growth of prentul cayenne pepper seedlings. Low to moderate doses (50–200 Gy) reduced viability, whereas moderate doses (250–400 Gy) had a stimulatory effect similar to the control. The highest mortality occurred at a dose of 200 Gy, which is close to the LD??, thus potentially generating genetic diversity. At high doses (>400 Gy), MGT increased sharply, and seedling growth was severely inhibited by physiological damage. Thus, the dose range of 200–300 Gy can be considered the optimum dose for mutation induction in prentul cayenne pepper.